A branch-and-bound algorithm for the two-machine total completion time flowshop problem subject to release dates - Rakrouki, Mohamed Ali; Kooli, Anis; Chalghoumi, Sabrine; Ladhari, Talel (Operational research, 2020)
We consider the problem of minimizing the sum of completion times in a two-machine permutation flowshop problem subject to release dates. We derive several lower bounds as well as a branch-and-bound algorithm for the problem under consideration. Computational experiments, on a large set of randomly generated instances, provide evidence that the proposed procedure performs consistently well.